RNA m6A Modification in Immunocytes and DNA Repair: The Biological Functions and Prospects in Clinical Application - Zhou, Mingjie; Liu, Wei; Zhang, Jieyan; Sun, Nan (Frontiers in Cell and Developmental Biology, 2021)
As the most prevalent internal modification in mRNA, N6-methyladenosine (m6A) plays broad biological functions via fine-tuning gene expression at the post-transcription level. Such modifications are deposited by methyltransferases (i.e., m6A Writers), removed by demethylases (i.e., m6A Erasers), and recognized by m6A binding proteins (i.e., m6A Readers). The m6A decorations regulate the stability, splicing, translocation, and translation efficiency of mRNAs, and exert crucial effects on proliferation, differentiation and immunologic functions of immunocytes, such as T lymphocyte, B lymphocyte, dendritic cell (DC) and macrophage. Recent studies have revealed the association of dysregulated m6A modification machinery with various types of diseases, including AIDS, cancer, autoimmune disease and atherosclerosis. Given the crucial roles of m6A modification in activating immunocytes and promoting DNA repair in cells under physiological or pathological states, targeting dysregulated m6A machinery holds therapeutic potential in clinical application. Here, we summarize the biological functions of m6A machinery in immunocytes and the potential clinical applications via targeting m6A machinery.